Phonaesthetic Phonological Iconicity in Literary Analysis Illustrated by Angela Carter’s “The Bloody Chamber” - Gwóźdź, Maja (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2014)
The article offers a phonosemantic analysis of Angela Carter’s “The Bloody Chamber.” The phonosemantic investigation has been based on the corpus of nineteen relevant sound-related descriptions of the sea. Although most excerpts identified contain aural metaphors and are not phonologically iconic per se, there seem to exist at least three fragments which are particularly interesting from a phonosemantic point of view. Most notably, phonaesthemes /gl/, /l/, /r/ have been found to carry substantial meaning contributing to the overall interpretation of the story in question. Accounting for the inevitable subjectivity concerning iconicity, and in this case phonological iconicity, a few theories are presented in order to support the author’s reading of each phonaestheme’s contextual significance. The paper briefly reviews the chronological development of the field of phonosemantics and then combines the aural images theory (proposed by Richard Rhodes) with the “aural semiotic process” theory (the term coined by the author). Each analysis is further supplemented with scholarly views on respective phonaesthemes. On the whole, the paper does not aim to polemicize with the well-established definition of a phoneme and its generally accepted arbitrariness. Nevertheless, it has been observed that a speculative phonosemantic analysis of a literary work may yield noteworthy results.